EVALUATION OF INSECTICIDES AGAINST COTTON WHITEFLY, BEMISIA TABACI (GENN.) (HOMOPTERA: ALEYRODIDAE) - Razaq, Muhammad; Aslam, Muhammad; Sharif, Kashif; Salman, Bakhtiar; Aleem, M. Faraz (Journal of Research (Science), 2003)
The experiment was conducted to evaluate the efficacy of Imidacloprid (Confidor 200SL), Acetamaprid (Mospilon 20SP), Methamidophos (Tamaron 600SL), Endosulfan (Thioluxon 35EC), Buprofezin (Sitara 25WP), Fenpropathrin (Fenthrin 20EC) and Diafenthiuron (Polo 500 SC) against whitefly, Bemisia tabaci (Genn.) on cotton variety CIM-473 during the crop year 2002. The crop was sprayed twice in September. After seven days of the first spray, the lowest population (0.6/leaf) of whitefly was observed in plots treated with Endosulfan 35EC followed by Acetamaprid 20SP(1.1/leaf), while the plots receiving Buprofezin 25 WP + Fenpropathrin 20 EC, Methamidophos 600SL and Imidacloprid 200SL had population of whitefly statistically similar. Seven days after second spray Acetamaprid 20SP and Diafenthiuron 500SC treated plots had the lowest population (1.4 per leaf) of whitefly followed by Imidacloprid 200SL (1.8 per leaf) and Fenpropathrin 20EC (1.9 per leaf).